Complementary Role of Historians and Geographers In the Study of Settlements: The Complementary Relationship Between History and Geography in the Study of Rural Settlements (Journal of Advances and Scholarly Researches in Allied Education, 2014)
History is thestory of human experience; it encompasses other human centred disciplines suchas anthropology, economics and geography. The relationship between history andgeography is especially intimate. None of them can be understood in the absenceof the other, so it only makes sense to study them together. Separation ofthese two subjects is arbitrary, anti-intellectual and ineffectual. The presentpaper intends to analyse the geographical approaches in the study of ruralsettlements. It is suggested that the integrative approach to study thesettlements is much of use instead of study in isolation.